Iridium-catalysed hydrosilylation of carbonyl derivatives: design and applications - Almehmadi, YA (2024)
Chapter 1: the tertiary amide is a ubiquitous functional group and plays an irreplaceable role in medicinal chemistry. Its robust nature has meant – in the past – that selective manipulation of this motif remained elusive. The reductive activation through hydrosilylation of tertiary amides – using Vaska’s complex (IrCl(CO)(PPh3)2) – has emerged as a powerful strategy for the chemoselective transformation of amides into reactive enamines and iminium ions. Furthermore, these synthetically valuable species can be accessed in the presence of traditionally more reactive functional groups. This approach to amide reductive activation via hydrosilylation has been exploited in a range of downstream C–C bond forming processes, and has seen significant applications in total synthesis, enabling streamlined routes for the synthesis of complex natural product architectures. This chapter covers the development of this synthetic strategy, from initial hydrosilylation studies, to its flourishing use in the reductive functionalization of amide-containing molecules, both simple and complex.